Simulasi Pelacakan Titik Daya Maksimum Modul Surya dengan Metode Grey Wolf Optimization - Rizki Faulianur; Ira Devi Sara; Fitri Arnia (Universitas Syiah Kuala, 2018)
The photovoltaic module has a nonlinear current and voltage characteristic curve where there is a maximum power point to be tracked to avoid wasted energy. Some methods for tracking the maximum power points have been developed such as perturb and observe (P O), Incremental Conductance (IC), and Hill Climbing (HC). However, those methods were not so accurate to find the maximum power point and they were also slow to respond the changes in solar radiation and temperature. To overcome the shortcomings of the method, a new optimization approach was developed. This method is called Gray Wolf Optimization (GWO). It work based on the wolf behavior in capturing the prey. In this study, it will be determined to what extent the GWO method can track the maximum working point of solar modules that undergo changes in radiation and working temperature quickly and accurately. This research was conducted by simulation using Matlab/Simulink by comparing the extract of power GWO method with its power characteristics. The results obtained by the GWO method trace maximum power with an average accuracy rate of 99.14 % with time less than 0.1 second. From this data, it can be concluded that the GWO method successfully responds well and accurately to changes in radiation and temperature.